Use of biologics for the management of Crohn's disease: IG-IBD clinical guidelines based on the GRADE methodology - Fabio Salvatore Macaluso; Claudio Papi; Ambrogio Orlando; Stefano Festa; Daniela Pugliese; Stefanos Bonovas; Claudia Pansieri; Daniele Piovani; Gionata Fiorino; Massimo Claudio Fantini; Flavio Caprioli; Marco Daperno; et al. (2023)
A cure for Crohn's disease (CD), a chronic inflammatory disease of the gastrointestinal tract of unknown etiology, is not available, so patients require lifelong management to keep inflammation under control. The therapeutic armamentarium has expanded with approval of several biological drugs, including infliximab, adalimumab, vedolizumab and ustekinumab - monoclonal antibodies that target different inflammatory pathways - and darvadstrocel, a suspension of expanded human allogeneic, adipose-derived, mesenchymal stromal cells for the treatment of refractory complex perianal fistula. Notwithstanding existing practice guidelines on medical therapy for CD, the Italian Group for the Study of Inflammatory Bowel Disease felt the need to issue new guidelines focused on the use of biologics for managing the intestinal manifestations of CD and based on the GRADE methodology. This document presents recommendations regarding six clinical settings, from the induction to the maintenance of clinical remission, and from optimization and de-escalation of treatments to dealing with perianal CD and post-operative recurrence. The 19 evidence-based statements are supported by information on the quality of the evidence, agreement rate among panel members, and panel comments mainly based on evidence from real world studies.